Optimal energy management of hybrid electric vehicles including battery aging - Serrao, Lorenzo; Onori, Simona; Sciarretta, Antonio; Guezennec, Yann; Rizzoni, Giorgio (Proceedings of the 2011 American Control Conference, 2011)
The paper presents a methodology to account for battery aging in the energy management strategy for a hybrid electric vehicle. An optimal control problem is formulated to minimize fuel consumption as well as battery aging, using recently developed methods for battery lifetime modeling. The approach relies on the concept of severity factor map, a tool used to quantify the aging effects of a battery due to its different on-vehicle operating conditions. The optimal control problem is solved using Pontryagin's Minimum Principle, showing with simulations the effect of the new control approach compared to the standard energy management strategies.